2013
DOI: 10.1097/qad.0b013e32835ce27e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measures of cardiovascular disease risk in antiretroviral treatment-naive individuals with HIV infection

Abstract: Objective To evaluate associations between traditional cardiovascular disease (CVD) risk factors, inflammatory markers, and markers of HIV disease activity with ultrasonographic measures of CVD risk in patients with HIV who are not receiving antiretroviral therapy (ART). Design Cross-sectional, baseline evaluation of ART-naïve HIV-infected individuals without known CVD or diabetes mellitus enrolled in a randomized ART treatment trial. Methods Prior to ART initiation, carotid artery intima-media thickness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
4
48
4
Order By: Relevance
“…In a study by Stein et al [29] ultrasonographic measures of CVD were used: carotid artery intima-media thickness and brachial artery flow-medicated vasodilation, to assess subclinical and functional atherosclerosis in treatment-naïve HIV-infected patients. They found that traditional CVD risk factors, such as aging, body size, and lipids levels, better predicted atherosclerosis than inflammatory markers, cytokines, CD4 cell count, and HIV viral load.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Stein et al [29] ultrasonographic measures of CVD were used: carotid artery intima-media thickness and brachial artery flow-medicated vasodilation, to assess subclinical and functional atherosclerosis in treatment-naïve HIV-infected patients. They found that traditional CVD risk factors, such as aging, body size, and lipids levels, better predicted atherosclerosis than inflammatory markers, cytokines, CD4 cell count, and HIV viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Current use of statins, fish oil (>2 g/day), fibric acid derivatives, or niacin (>1000 mg/day) was exclusionary at enrolment. Detailed inclusion and exclusion criteria for the study were reported previously in our baseline, cross-sectional analysis [16]. …”
Section: Methodsmentioning
confidence: 99%
“…B-mode images of the distal right common carotid artery (CCA) and the right carotid artery bifurcation were acquired with a high-resolution linear array ultrasound transducer with simultaneous electrographic tracings before ART initiation, and then after 48, 96, and 112–144 weeks [16]. The right CCA was imaged in cross-section and the transducer moved laterally into the jugular vein so they were stacked with the vein displayed on top of the artery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high-resolution ultrasound measures of carotid intima media thickness (CIMT) also predict CVD risk in the general population, particularly stroke[24, 25]. Traditional and non-traditional risk factors are associated with elevated CAC and CIMT in patients with HIV[8, 9, 22, 23, 2629]. To date, transcriptional modulators that may explain these observations have not been identified.…”
Section: Introductionmentioning
confidence: 99%